STATE MARRIAGE ASSISTANCE SCHEME OF JAMMU AND KASHMIR - Nargis Farheena Bashir,; Dr. Nirmal singh, (The Bioscan, 2025)
The State Marriage Assistance Scheme (SMAS) in Jammu and Kashmir is an important government program that benefits economically backward women through financial support to enable them to get married. This research identifies the socio-economic effect, awareness, access, and challenges in implementing the scheme using a descriptive and evaluative research methodology. Information gathered from 200 beneficiaries and 50 government officials via surveys, interviews, and focus group discussions underscore that although the scheme has benefited many lives—especially by providing financial relief, enhancing social status, and empowering women—there are still major challenges. These are low awareness, procedural challenges, and inconsistent guidance during the application process. The results emphasize the necessity of increased outreach, simplified procedures, and complementary schemes in education, employment, and health to enhance the effectiveness of the scheme. This research offers useful lessons for policymakers and stakeholders to enhance the design and implementation of welfare schemes to empower poor women.